Osteonecrosis of the Knee Due to Hypertriglyceridemia and Hyperuricemia: A Case Report - Duygu Geler Külcü; Safiye Tuncer (Archives of Rheumatology, 2007)
Osteonecrosis is a pathologic process which results with the death of bone and bone marrow elements. The main predisposing factors (trauma, glucocorticosteroids, alcoholism and connective tissue disorders) should be carefully sought but osteonecrosis can also be idiopathic in origin. We report a patient who developed osteonecrosis of the knee with hypertrigliceridemia and hyperuricemia. Knee osteonecrosis combined with hypertriglyceridemia is a rare condition. This case draws attention to the association between osteonecrosis and metabolic disorders. (Rheumatism 2007; 22: 114-6)